Self-Powered Dual-Color UV–Green Photodetectors Based on SnO2 Millimeter Wire and Microwires/CsPbBr3 Particle Heterojunctions - Zhang, Yong; Xu, Wenxin; Xu, Xiaojie; Cai, Jian; Yang, Wei; Fang, Xiaosheng (The journal of physical chemistry letters, 2019)
Multiband detection has always been a challenge and has drawn much attention in the development of photodetectors (PDs). Herein, we present controllable synthesis of SnO2 wires with different sizes via chemical vapor deposition and formed composites with CsPbBr3 particles to realize dual spectral response. We constructed PDs based on a single SnO2 millimeter wire decorated with CsPbBr3 particles (SnO2 MMW/CsPbBr3), which showed a stepped spectrum, fast response speed, and self-powered function. Meanwhile, SnO2 microwires/CsPbBr3 composites (SnO2 MWs/CsPbBr3) were also utilized to fabricate PDs. It is noteworthy that detection occurred in two different wavelength bands (320 and 520 nm) with equivalent intensity at a bias of 0 V. The self-powered feature of this device comes from the built-in electric field at the interface of SnO2/CsPbBr3, and the dual-color response originates from asymmetric junction barriers between conduction bands of SnO2 and CsPbBr3. This work demonstrated promising self-powered PDs that are capable of multiband detection.